Electrostatic cnoidal waves and soliton structures in multi‐ions plasmas. Issue 2 (8th October 2018) - Ur‐Rehman, Hafeez; Mahmood, S.
Abstract : Using a reductive perturbation technique (RPT), the Korteweg‐de Vries (KdV) equation for nonlinear electrostatic waves in multi‐ion plasmas is derived with appropriate boundary conditions. Furthermore, compressive and rarefactive cnoidal wave and soliton solutions are discussed. In our model, the multi‐ion plasma consists of light dynamic warm ions, heavy cold ions, and inertialess electrons, which follows the Maxwell‐Boltzmann distribution. It is observed that in such an unmagnetized multi‐ion plasma, two characteristic electrostatic waves i.e., slow ion‐acoustic (SIA) waves and fast ion‐acoustic (FIA) waves, can propagate. The results are discussed by considering two types of multi‐ion plasmas i.e., H + –O + –e plasma and H − –O + –e plasma that exist in space plasmas. It is found that for H + –O + –e plasma, the SIA cnoidal wave and soliton form both positive (compressive) and negative (rarefactive) potential pulses, which depend on the temperature and density of the light and warm ions. However, only electrostatic positive potential structures are obtained for FIA cnoidal wave and soliton in H + –O + –e plasma. In the case of H − –O + –e plasma, the SIA cnoidal wave and soliton form only compressive structures, while the FIA cnoidal wave and soliton compose rarefactive structures. The effects of light ions' density and temperature on nonlinear potential structures are investigated in detail. The parametric results are also demonstrated, which are applicable to space and laboratory multi‐ion plasma situations.